ASPECTE GENERALE PRIVIND POLUAREA AERULUI (PANGEEA, 2025)
The atmospheric air is one of the essential primary components of the environment. Air composition remained almost unchanged since the early Proterozoic Eon to the industrial revolution. In particular the last century has brought important changes in the composition of air. They cause changes in all other parts of the environment. The paper attempts a synthesis of air pollution issues nationally and globally and the current status of this phenomenon. I finally made some conclusions about these issues and the possibilities of overcoming them.